Hereditary neuropathy with liability to pressure palsies: a case series report - Naudžiūnaitė , S.; Bunevičiūtė , R.; Burnytė , B. (Neurologijos seminarai, 2020)
Hereditary neuropathy with liability to pressure palsies (HNPP) is an autosomal dominant inherited peripheral nerve disorder characterized by recurrent, episodic local reversible peripheral nerve compression neuropathy that occurs spontaneously or after minor trauma.We describe demographic, clinical, and electrophysiological data of seven patients from six families (ages 17 to 74 years) diagnosed with HNPP. All patients had a genetically proven diagnosis of a deletion at 17p12 locus, which contains PMP22 gene. In five patients (71.4%), the first symptoms of HNPP (hypoesthesia, numbness, episodes of pain, and weakness) started in the second or third decade of life. One asymptomatic patient was diagnosed with HNPP based on a positive family history. Three patients (42.9%) reported that symptoms were caused by direct mechanical compression of the nerve. Three patients (42.9%) were found to have atrophy of the legs (calves or feet), hammer deformities of the toes, and pes cavus. Foot drop was observed in four patients (57.1%). In five patients, electroneurography showed signs of demyelinating type, in one – mixed (predominantly axonal).This study highlights the diversity of the clinical course of HNPP and the importance of early diagnosis including electrophysiological studies and genetic testing of copy number variation at 17p12 locus, which can prevent clinical manifestations of the disease and/or complications.
Keywords: compression neuropathy; hereditary neuropathy with liability to pressure palsies; PMP22 gene